Mass Spectral Fragmentation of 2N-Propargyl (1,2,4)-Triazolo (3,4-b)- Benzolthiazol-3-One - Deshmukh, M.V. (Asian Journal of Chemistry, 2010)
An interesting mass spectral fragmentation of 2N-propargyl (1,2,4)-triazolo (3,4-b)-benzothiazole is discussed. In one of the pathways retero Diels Alder fission is reported.